Ecotoxicological tests with Eisenia fétida for the evaluation of areas allegedly contaminated with oil derivates in municipality of João Monlevade/MG (Research, Society and Development, 2020)
Soil contamination can occur due to inadequate disposal of solid waste, by various industrial activities, and this can directly or indirectly affect water bodies, fauna, vegetation and the air. The contamination of the soil by petroleum derivatives has been intensively studied, due to the concern in relation to environmental risks, mainly when it comes to the sale of oil and the logistics of production and distribution of its derivatives. To assess the effects of chemical substances on terrestrial ecosystems, ecotoxicological tests can be used as a tool for monitoring contamination in a given area and to demonstrate the effectiveness during a remediation process. In such studies, the earthworm species Eisenia fetida is widely used as a test organism. Thus, the objective of this work was to analyze the applicability of ecotoxicity bioassays using Eisenia fetida to assess the toxicity of soils supposedly contaminated by oil derivatives in the city of João Monlevade. In the behavior test, only samples of soil P1 can be considered conducive to the survival of this species. The analysis of the mortality percentage of Eisenia fetida in the lethality test showed that statistically the results have no significant difference; in the analysis of final biomass, soils P2, P3 and P4 were considered statistically equal and soil P5 (control) was different from the others. In P4 soils, it was possible to observe a change in the color of earthworms, indicating a possible sub-lethal effect, caused by the presence of toxic agents in the soil. The reproduction test showed that the P1 and P5 soils were the only ones favorable to reproduction, which can be evidenced by the presence of cocoons and young. The results suggest that Eisenia fetida is a sensitive bioindicator for assessing the contamination of terrestrial ecosystems by oil and oil products.